Synthesis, Characterization, and Photocatalytic Activity of N-Doped ZnO/ZnS Composites. (16th January 2013) - Ma, Hongchao; Cheng, Xiaohong; Ma, Chun; Dong, Xiaoli; Zhang, Xinxin; Xue, Mang; Zhang, Xiufang; Fu, Yinghuan
Abstract : The aim of the present study is to enhance photocatalytic performance of ZnO semiconductor by comodification with doping of nonmetal ions and coupling with another semiconductor. Therefore, we synthesized the N-doped ZnO/ZnS photocatalysts via a simple heat-treatment approach using L-cysteine as N and S source in this work. Anthraquinone dye (reactive brilliant blue KNR) is employed as the model contaminants to evaluate the photocatalytic activity of as-synthesized samples under sunlight illumination. The N-doped ZnO/ZnS synthesized by this method shows better photocatalytic activity as compared to that of pure ZnO. The enhanced photocatalytic activity of the N-doped ZnO/ZnS composites may be related to the existence of N doping, ZnS/ZnO heterostructure, and covered abundant carbon species on the photocatalyst surface, which causing high absorption efficiency of light, efficient separation of electron-hole pairs, and quick surface reaction in doped ZnO.